How to report the results of public health research - Habibzadeh, Farrokh (Journal of Public Health and Emergency; Vol 1 (December 2017): Journal of Public Health and Emergency, 2017)
“What can be asserted without evidence can also be dismissed without evidence.”—Christopher Hitchens [1949–2011], British journalist and writer (1).